2019
DOI: 10.1186/s13104-019-4147-x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of under-five children born to teenage mothers in an urban setting, south-western Nigeria

Abstract: Objective There have been many studies on the nutritional status of under-fives and factors responsible but very few looks at this special group of women. This study assessed the breastfeeding practices of teenage mothers and determined its association with the nutritional indices of their under-five children. The study was a descriptive cross-sectional survey. A total of 300 mother–child pair was selected using a multi-stage sampling technique from Primary Health Care centres in Ondo West Local G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…If maternal education is to play a significant role in reducing child malnutrition, women need to be educated beyond the primary school level. Monthly income distribution of the respondents' parents showed that a greater percentage earned between ₦50,000-100,000 which corresponds with recent study by Olodu et al (2019) [5] on a higher monthly income more than ₦20,000, while 38.4% earned above ₦100,000. This is in accordance with reports by Mathieson and Koller, (2016) [6] who stated that healthy eating habits are largely determined by social, economic and cultural factors (such as place of residents) that influence access, availability and uptake.…”
Section: Nutritional Status Of the Under 5 Children By Sexsupporting
confidence: 89%
“…If maternal education is to play a significant role in reducing child malnutrition, women need to be educated beyond the primary school level. Monthly income distribution of the respondents' parents showed that a greater percentage earned between ₦50,000-100,000 which corresponds with recent study by Olodu et al (2019) [5] on a higher monthly income more than ₦20,000, while 38.4% earned above ₦100,000. This is in accordance with reports by Mathieson and Koller, (2016) [6] who stated that healthy eating habits are largely determined by social, economic and cultural factors (such as place of residents) that influence access, availability and uptake.…”
Section: Nutritional Status Of the Under 5 Children By Sexsupporting
confidence: 89%
“…Olodu et al conducted study in Nigeria found that prevalence of stunting; wasting and underweight is 18.6%, 25.3, and 29.5%. 5 In a study conducted by Chataut et al in rural Nepal, 7% wasted, 39.9% stunted and 18.9% underweight. 6 In a study conducted by the Alom et al in Bangladesh, 16% severely stunted, 25% moderately stunted, 3% severely wasted, 14% moderately wasted, 11% severely underweight and 28% moderately underweight.…”
Section: Discussionmentioning
confidence: 97%
“…This explains why adolescent mothers are likely to give birth to preterm, low-birthweight babies and with an increased likelihood of infant deaths compared to those born with mothers aged 20 years and above [14]. Furthermore, the high rates of teenage pregnancy contribute significantly to the high prevalence of malnutrition among adolescents themselves and their under-five children [15]. Adolescent mothers are not only challenged by the physical threats to their health, but also socially [16].…”
Section: Discussionmentioning
confidence: 99%